Northern Hemisphere - Wyld, James, 1790-1836 (Cartographer)
Map of the Northern Hemisphere with hand coloured divisions of countries, colonies, and political divisions of the time. Shows general areas of mountain ranges, large lakes and rivers, and place names. Originally published : A general atlas of modern geography, consisting of a complete collection of the most approved maps of the four quarters of the globe, subdivided according to their respective states and coloured to show the new limits. Relief shown pictorally. Limited details of the Arctic. Longitude from the 10 Meridian of Greenwich Published by Js. Wyld (successor to Mr. Faden) Geographer to the King and to H.R.H. the Duke of York, Charing Cross, March 1st 1824. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Depicts the globe from an Arctic perspective, ending at the equator.